2020
DOI: 10.3389/fcell.2020.584497
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells Early Response to Low-Dose Ionizing Radiation

Abstract: IntroductionMesenchymal stem cells (MSCs) are applied as the therapeutic agents, e.g., in the tumor radiation therapy.Purpose of the StudyTo evaluate the human adipose MSC early response to low-dose ionizing radiation (LDIR).Materials and MethodsWe investigated different LDIR (3, 10, and 50 cGy) effects on reactive oxygen species production, DNA oxidation (marker 8-oxodG), and DNA breaks (marker ɣ H2AX) in the two lines of human adipose MSC. Using reverse transcriptase–polymerase chain reaction, fluorescence-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 60 publications
1
7
0
1
Order By: Relevance
“…To sum, low-dose X-ray radiation, as well as oxidized cfDNA, lead to short-term intracellular oxidative stress. We have previously shown that an increase in intracellular ROS is a consequence of the activation of NADPH oxidases, one of which is NOX4 [ 21 , 22 , 23 ]. Another source of intracellular ROS is a mitochondrial respiratory chain.…”
Section: Resultsmentioning
confidence: 99%
“…To sum, low-dose X-ray radiation, as well as oxidized cfDNA, lead to short-term intracellular oxidative stress. We have previously shown that an increase in intracellular ROS is a consequence of the activation of NADPH oxidases, one of which is NOX4 [ 21 , 22 , 23 ]. Another source of intracellular ROS is a mitochondrial respiratory chain.…”
Section: Resultsmentioning
confidence: 99%
“…It can be speculatively assumed that NOX4 gene over-expression in the lymphocytes of some SZ patients results from the development of an adaptive response improving cell survival under conditions of oxidative stress, which is aggravated during disease exacerbation. We discussed earlier that the response of schizophrenic lymphocytes to endogenous oxidative stress is very similar to the response of healthy donor cells to the low doses of ionizing radiation (LDIR) [ 20 , 49 ]. Indeed, NOX4 gene expression seemed to elevate significantly in both in differentiated and stem human cells within the first hours after LDIR exposure [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, low-dose responses clearly differ in normal and cancer cells [ 484 ]. In fact, in quiescent cancer stem cells, low doses may as act “wake-up” signals [ 485 , 486 ]. C-ions and miRNAs may inhibit them [ 487 ].…”
Section: Discussionmentioning
confidence: 99%